Migration and Remittances : Recent Developments and Outlook - Ratha, Dilip; De, Supriyo; Plaza, Sonia; Schuettler, Kirsten; Shaw, William; Wyss, Hanspeter; Yi, Soonhwa (Washington, DC: World Bank, 2016)
The April 2016 issue of the Brief provides an update of the detailed estimates of remittances for 2015 and new projections for 2016-18. A special topic for this brief is a discussion of how migration outflows, temporary return, and remittances help households and societies cope with natural disasters and epidemics.